2012
DOI: 10.7863/jum.2012.31.10.1589
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Appearances of Soft Tissue Angioleiomyomas

Abstract: Objectives The purpose of this study was to evaluate the sonographic features of angioleiomyomas with priority given to the vascular pattern to help in the differential diagnosis from other hypervascular soft tissue tumors. Methods The inclusion criteria for this retrospective and nonblinded study were fulfilled in 33 patients with circumscribed hypervascular soft tissue tumors based on pathologic identification. Thirteen cases were angioleiomyomas; 9 cases were nonsubungual glomus tumors; and 11 cases were he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…The ultrasonographic findings of angioleiomyoma are well-established in the literature and include an oval shape, a well-defined margin, a homogeneous echotexture, hypoechogenicity, and moderate or high vascular density ( 3 5 10 ). In our study, angioleiomyomas were also frequently well-defined, oval-shaped, homogeneous, and hypoechoic.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The ultrasonographic findings of angioleiomyoma are well-established in the literature and include an oval shape, a well-defined margin, a homogeneous echotexture, hypoechogenicity, and moderate or high vascular density ( 3 5 10 ). In our study, angioleiomyomas were also frequently well-defined, oval-shaped, homogeneous, and hypoechoic.…”
Section: Discussionmentioning
confidence: 97%
“…Rich hypervascularity with diffusely scattered irregular vessels is commonly observed in non-subungual glomus tumors ( 1 3 9 11 ). In the series reported by Park et al ( 3 ), a specific tumor vascular pattern (several clustered linear vessels that converged at a single point) was a statistically significant finding for angioleiomyoma among hypervascular masses (hemangioma and non-subungual glomus tumor) as based on color Doppler imaging. In the English literature published to date, there are no reported specific sonographic features or differential diagnostic clues for atypical imaging features of angioleiomyomas, such as isoechoic masses with little vascularity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common presentation of ALM is a painful, solid, solitary subcutaneous nodule. It is mostly encountered in females in their second to sixth decade of life [ 4 ]. These lesions are slow growing and may take 10–15 years for patients to seek medical attention for the mass [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that the typical sonographic features of angioleiomyoma may include an oval shape, well-defined margins, a homogenous structure, and hypervascularity. By contrast, some studies reported that angioleiomyoma may show low or moderate vascular density 3 4 .…”
mentioning
confidence: 91%